Penguatan Pengelolaan Museum Budaya Rambu Solo Ne’ Gandeng Melalui Workshop dan Pelatihan Media Sosial, Manajemen SDM, dan Keuangan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This activity aims to strengthen the management of the Rambu Solo Ne' Gandeng Cultural Museum through workshops and training on social media management, human resource management, and simple and responsible museum financial management. This activity was carried out to increase the capacity of museum managers to promote the museum through social media, manage human resources professionally, and understand the basic principles of financial management to support museum sustainability. The methods used included material delivery, interactive discussions, and case studies tailored to the museum's conditions and needs. Furthermore, this activity emphasized a family-like and contextual approach to ensure the material was easily understood and applied by participants. The activity took place on September 9-10, 2025, with 18 participants. The expected outcome of this activity is an increased understanding of museum managers in social media, human resource management, and financial management, so that the Rambu Solo Ne' Gandeng Cultural Museum can be managed in a more organized, transparent, and sustainable manner as an institution for preserving Torajan culture.